2019
DOI: 10.1016/j.kint.2018.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Safety and cardiovascular efficacy of spironolactone in dialysis-dependent ESRD (SPin-D): a randomized, placebo-controlled, multiple dosage trial

Abstract: C ardiovascular disease underlies the majority of deaths in patients with dialysis-dependent end-stage renal disease (ESRD). 1 Standard cardiovascular therapies have rarely been tested in this population and with disappointing results. For example, 3 trials of HMG-CoA reductase inhibitors found that neither overall nor cardiovascular mortality was reduced in hemodialysis (HD) patients treated with statins compared with placebo. 2-4 These and other findings highlight the need to evaluate therapies to reduce car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 24 publications
(30 reference statements)
1
67
2
Order By: Relevance
“…Nonetheless, some studies yielded negative results, including showing no benefit in BP control or reductions in LVMi, which gave us pause on drawing firm conclusions. This past year saw the publication of two more RCTs, safety and cardiovascular efficacy of spironolactone in dialysis-dependent ESRD (SPin-D) (6) and Mineralocorticoid Receptor Antagonists in End-Stage Renal Disease (MiREnDa) (7), examining the effects of spironolactone in patients on chronic hemodialysis. Although both these RCTs showed relative safety regarding hyperkalemia, they failed to show improvements in cardiac diastolic function over 36 weeks (6) or in LVMi over 40 weeks (7) with spironolactone use.…”
Section: Aldosterone Antagonists In Eskdmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, some studies yielded negative results, including showing no benefit in BP control or reductions in LVMi, which gave us pause on drawing firm conclusions. This past year saw the publication of two more RCTs, safety and cardiovascular efficacy of spironolactone in dialysis-dependent ESRD (SPin-D) (6) and Mineralocorticoid Receptor Antagonists in End-Stage Renal Disease (MiREnDa) (7), examining the effects of spironolactone in patients on chronic hemodialysis. Although both these RCTs showed relative safety regarding hyperkalemia, they failed to show improvements in cardiac diastolic function over 36 weeks (6) or in LVMi over 40 weeks (7) with spironolactone use.…”
Section: Aldosterone Antagonists In Eskdmentioning
confidence: 99%
“…With that caveat, several trials suggest that spironolactone at a daily dose of 25 mg is likely to be safe in ESKD. However, the risk of hyperkalemia seems elevated with the 50-mg daily dose (6). Safety profile may be more favorable in peritoneal dialysis, where hyperkalemia is less of a concern compared with hemodialysis (10).…”
Section: Aldosterone Antagonists In Eskdmentioning
confidence: 99%
“…These studies are limited by few HFrEF patients, small sample sizes, under‐recruitment, low event rates, and use of surrogate outcomes such as left ventricle mass and left ventricular ejection fraction. These trials have several notable findings: (a) a slightly higher frequency of moderate hyperkalemia and rare occurrence of life‐threatening hyperkalemia 68‐70 ; and (b) no increase in hypotension requiring hospitalization 71 . The Mineralocorticoid Receptor Antagonist in End‐Stage Renal Disease (MiREnDa) study found no difference in LV mass or LVEF between those on spironolactone versus placebo, though only 4% of patients had heart failure at study entry 72 .…”
Section: Pharmacologic Management Of Hfrefmentioning
confidence: 99%
“…5 Upstream this trial, relatively smallsized and short-term trials suggested an acceptable safety profile of MRAs in relation to potassium and blood pressure and even a beneficial effect on CV structure and function. 6 In this issue, Charytan et al 7 (2019) report results of the randomized placebo-controlled double-blind Spin-D trial. This was an early-phase, doseranging safety and efficacy trial, of the MRA spironolactone (12.5, 25, 50 mg/ d), conducted in 129 chronic HD patients followed for up to 36 weeks.…”
mentioning
confidence: 99%